(untitled) (JIIP - Jurnal Ilmiah Ilmu Pendidikan, 2024)
This study aims to explore the learning methods of current Gen Z students, particularly at the high school level, and their expectations regarding classroom teaching approaches. The study adopts a qualitative approach, where data are collected and analyzed through words and descriptions. An incidental sampling technique is applied to select samples based on coincidence. The four questions outlined by Messineo et al. (2007) were utilized to gauge the learning method expectations of Gen Z students. The results indicate that the predominant teaching method in schools is teacher-centered, with a focus on the interaction between the teacher and students. The learning methods preferred by Gen Z students, however, include student-centered learning, instructional strategies that emphasize teacher-student interaction, and teacher-centered approaches. Additionally, Gen Z students express a preference for incorporating technology in the classroom.